The Settlement Of Criminal Disputes Disputes Under National Law Andcustomary Criminal Law In Baturaja Village Community Of Pondok Kubang Sub-District In Central Bengkulu - Silviani, Yessi; Royani, Ferawati; Aprianto, Sandi (Fakultas Hukum Dehasen, 2026)
Sanctions in customary criminal law can be in the form of traditional punishments, such as fines, purification, or ostracism from the community. The formulation of the problem taken in this study is How is the resolution of criminal disputes in the law and customary criminal law in the community of Baturaja Village of Pondok Kubang Sub-District in Central Bengkulu? What are the inhibiting factors in the resolution of criminal disputes in the law and customary criminal law in the community of Baturaja Village of Pondok Kubang Sub-District in Central Bengkulu? The research method in this thesis is an empirical legal method. The empirical approach is used to determine the practice of resolving criminal cases according to customary law that applies in the community. Conclusion Settlement of criminal cases through customary law is a process of resolving cases outside the courts which consists of first, a mediation system with a consensus approach through deliberation. Second, a restorative justice system, a case resolution system with the intention of restoring the conditions arising from the victim therefore a sense of brotherhood between each party is woven back together. The main objective of resolving violations of customary criminal acts is not based on a retributive view (retribution); but as a means of resolving conflicts, maintaining harmonious conditions among community members, and maintaining solidarity.